Global Dependence Analysis on Indonesian Palm Oil Production and Its Effect on Environmental Security Using the Copenhagen School Approach - Bogheiry, Ali; Thaha, M; Rahmah, Laila (Riviera Publishing, 2023)
Increasing international demand is related to global dependency on Indonesian palm oil, forcing Indonesia to increase its palm oil production, resulting in environmental concern. A combination of quantitative and qualitative methods with the Copenhagen School approach is used. On average from 2010-2020, Indonesia exported palm oil to Asia (64.72%), the EU (16.29%), Africa (13.59%), America (5.30%), and Oceania (0.07%). According to the Copenhagen School perspective, there are potential environmental security threats to the international world. One aspect of the environment that is suffering is forested due to deforestation, related fires, damage to ecosystems, and species that are essential contributors to global climate change and loss of biodiversity, as well as poor local and regional air quality. Involvement in the human rights sector, terrorist activities, smuggling, and tax evasion are also evident. Indonesian palm oil production provides economic benefits through international trade and at the same time threatens global environmental security.